Penerapan E-Filing, Peran Relawan Pajak dan Kesadaran Wajib Pajak terhadap Kepatuhan WPOP Dalam Melaporkan SPT Tahunan - Yolanda Pratami (Jurnal Ilmiah Akuntansi Universitas Pamulang, 2022)
In order to fulfil tax obligations and improve taxpayer compliance from year to year, DJP cooperates with universities to establish a Tax Center and a tax volunteer program. This study aims to empirically examine the effect of implementing e-filing, tax volunteers and taxpayer awareness on individual taxpayer compliance in reporting Annual Tax Returns at the Riau Islamic University Tax Center. WPOPs who report their annual tax returns at the Riau Islamic University Tax Center are the population in this study. The sample collection method is a purposive sampling of as many as 96 samples. Technical analysis of the data in this study using multiple regression analysis with the help of the SPSS program. The results of the studies prove that the implementation of e-filing and taxpayer awareness partially affects individual taxpayer compliance when the role of tax volunteers does not affect individual taxpayer compliance. Furthermore, the application of e-filing, the tax volunteers' role and the awareness of taxpayers simultaneously affect the compliance of individual taxpayers in reporting the Annual SPT.